Improving Children’s Logical and Mathematical Performance via a Pragmatic Approach - Bagassi, Maria; Salerni, Nicoletta; Castoldi, Valeria; Sala, Valentina; Caravona, Laura; Poli, Francesco; Macchi, Laura (Frontiers in Education, 2020)
Deductive and logical reasoning is a crucial topic for cognitive psychology and has largely been investigated in adults, concluding that humans are apparently irrational. Yet, from a pragmatic approach, the logical level of meaning is only one of possible communicative interpretations, and the least likely to be assigned if the intent of the task is not adequately transmitted. Indeed, new formulations of the mathematical tasks (syllogisms, selection task, class inclusion task, prolem solving), of greater relevance to the problem and to its aim, greatly improved adults’ logical performance. The current study tested whether pragmatic manipulations of task instructions influenced in a similar way children’s performance in deductive and logical tasks (Experiment 1) and in insight problems (Experiment 2). We found that, when task instructions were in accordance with the conversational rules of communication, 10-year-old children substantially improved their performance. We suggest that language use imposes constraints in terms of informativeness and relevance which are crucial in teaching logic and mathematics.